43-3 (5 mũ 3 : 5 mũ 2 + 5 . (-4 ) – 2 mũ 2

43-3 (5 mũ 3 : 5 mũ 2 + 5 . (-4 ) – 2 mũ 2

2 bình luận về “43-3 (5 mũ 3 : 5 mũ 2 + 5 . (-4 ) – 2 mũ 2”

  1. 43-3 (5 mũ 3 : 5 mũ 2 + 5 . (-4 ) – 2 mũ 2
    =43-3[5 mũ 1 + (-20)-4]
    =43-3[5+(-20)-4]
    =43-3.(-19)
    =43-(-57)
    =100
    xin 5 sao hay nhất ạ
     

    Trả lời
  2. Giải đáp + Lời giải và giải thích chi tiết:
    43-3[5^3:5^2+5*(-4)-2^2]
    =43-3[5+(-20)-4]
    =43-3[(-15)-4]
    =43-3*(-19)
    =43-(-57)
    =43+57
    =100

    Trả lời

Viết một bình luận

Câu hỏi mới